Initial Renal Function (eGFR) Is a Prognostic Marker of Severe Acute Pancreatitis: A Cohort-Analysis of 1,224 Prospectively Collected Cases - Tod, Pál; Farkas, Nelli; Németh, Dávid; Szénási, Gábor; Vincze, Áron; Hágendorn, Roland; Czakó, László; Illés, Dóra; Izbéki, Ferenc; Dunás-Varga, Veronika; Papp, Mária; Hamvas, József; et al. (Frontiers in Medicine, 2021)
Abstract Background Acute pancreatitis (AP) is a life-threatening disease. We aimed to explore the prognostic relevance of renal function based on estimated glomerular filtration rate (eGFR). Methods A prospective registry of AP patients was established by the Hungarian Pancreatic Study Group. Data of 1224 consecutive patients were collected between 2012 - 2017. Patients were divided into 3 groups according to their eGFR measured within 24 hours of hospitalization: normal renal function: >90 mL/min, mild to moderate renal functional impairment: 30-90 mL/min and severe renal dysfunction: <30 mL/min. Associations of eGFR with outcome (survival, length of hospitalization, AP severity, blood glucose), inflammatory markers (erythrocyte sedimentation rate, white blood cell count), anemia and organ failure (heart, kidney, liver) were analyzed. Results Death, longer hospitalization and severe AP, but not the cause of AP, were significantly associated with lower eGFR. The inflammatory markers (CRP, WBC count) but not anemia (Hb, Htk) were closely associated with severe renal dysfunction. Renal function was associated with heart and renal failure but not with other complications of AP such as respiratory failure, local pancreatic complications, diabetes or peptic ulcer. eGFR was not associated with liver damage (ALAT, γ-GT) or liver function (serum bilirubin) although biliary complications, alcohol and metabolic syndrome were the most common etiologies of AP. Conclusions Our study suggests a useful prognostic value of initial eGFR in AP patients. Even mild eGFR reduction predicted mortality, severity of AP and the length of hospitalization. Thus, precise evaluation of renal function should be considered for assessing AP severity and outcome.